Peran Penyidik Terhadap Tindak Pidana Pencetak Dan Pengedar Uang Palsu (Studi Kasus Polres Gorontalo Kota) - febian, febian saputra yantu; Darmawati, Darmawati; Andini, Nur Qalbi (Fakultas Hukum Universitas Ichsan Gorontalo, 2025)
This research aims to determine (1) the role of investigators concerning perpetrators involved in the criminal acts of printing and circulating counterfeit money and (2) the obstacles experienced by investigators when investigating these criminal acts. This research employs an empirical legal research method that examines law in its practical application and analyzes how law functions within the community. The findings indicate that: (1) Investigators encounter difficulties in gathering sufficient and valid evidence to prove the criminal acts committed by suspects. Besides that, advancements in increasingly sophisticated counterfeiting technology present additional challenges in identifying counterfeit money. (2) Another significant obstacle is the weak coordination among law enforcement agencies. Differences in procedures, policies, and interests among these agencies frequently impede effective coordination. Lack of communication and inter-agency rivalry also worsen the situation, thereby hindering the effective investigation of the criminal acts of printing and circulating counterfeit money.